Glycated haemoglobin - when can we trust it? Analysis of factors affecting the HbA1c level - Marcin Lewicki; Łukasz Chołuj; Marta Molendowska; Zuzanna Czarnota; Rafał Mazur; Mateusz Tyniec; Agata Barbara Smoleń (Kazimierz Wielki University, 2018)
Epidemiological data leaves no illusions - diabetes mellitus is a real epidemic of a non-communicable disease. Glycated haemoglobin was isolated with chromatography column as a separate subtype of haemoglobin as early as in 1958. An increase in its concentration in response to hyperglycaemia has already been recognized in 1969. Glycated hemoglobin (HbA1c) is a routinely used marker for long-term glycemic control in patients with diabetes. With HbA1C measurement we are able to retrospectively assess the average blood glucose levels. HbA1c correlates well with the risk of long-term diabetes complications. However, HbA1C levels may sometimes be misleading as a reliable measure of glycemic control. HbA1c values measurements are prone to diagnostic interference with many factors. The aim of this review was to present the numerous clinical scenarios in which the use of HbA1c levels alone for either diagnosis or as a marker of glycemic control, may lead to false assumptions.